(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the interpretation of the figure of Khidr (peace be upon him) in religious, philosophical, and literary sources based on the Qur’an and Islamic narratives. It highlights how the image of Khidr has been shaped in Uzbek classical and contemporary literature, as well as in folk oral tradition, and what ideological and aesthetic significance it carries.